Cytokeratin 20 positive circulating tumor cells are a marker for response after neoadjuvant chemoradiation but not for prognosis in patients with rectal cancer. Issue 1 (December 2015) - Hinz, Sebastian; Röder, Christian; Tepel, Jürgen; Hendricks, Alexander; Schafmayer, Clemens; Becker, Thomas; Kalthoff, Holger
Abstract Background Several studies have shown, that circulating tumor cells (CTC) have a negative prognostic value in colorectal cancer patients. Aim of this study was to evaluate the role of CTC in specifically rectal cancer patients regarding the influence on overall survival and to elucidate the impact of CTC in predicting response after chemoradiation (RCTX). Methods In this prospective monocentric study 267 patients with rectal cancer were included. Patients with locally advanced tumors were treated with RCTX followed by surgery. The primary endpoints were: Evaluation of CTC at the time of surgery and correlation with main tumor characteristics, response to neoadjuvant RCTX and overall survival (OS). CTC were detected in the blood using CK20 RT-PCR. Results Sixty-three patients were treated with neoadjuvant RCTX. In 46.8 % of the patients receiving neoadjuvant RCTX CTC were detected, which was significantly higher than in the group without RCTX (p  = 0.002). Histopathologic regression after RCTX was evident in 27.8 % of the patients. In the subgroup of responders after RCTX we found CTC at a significantly lower rate than in non-responders (p  = 0.03). No significant association was found between CTC detection and tumor characteristics and OS. The OS was significantly improved for responders compared to non-responders (p  = 0.007). Conclusions Responders after neoadjuvant RCTX had a lower incidence of CTC compared to non-responders, which might be a result of effective systemic and local treatment prior to surgery. Interestingly, detection of CTC did not correlate with tumor stage and OS, which is in contrast to previous reports of patients with colon cancer.